Этилен в прогамной фазе оплодотворения у высших растений - Ковалева, Л.В.; Захарова, Е.В.; Тимофеева, Г.В.; Устинова, А.В.; Ракитин, В.Ю. (Фактори експериментальної еволюції організмів, 2013)
Aims. Physiological role of ethylene in the gametophyte-sporophyte interactions remains unknown. Methods. The ethylene production in the course of male gametophyte development and germination, in vitro and in vivo, in petunia fertile (self-compatible and self-incompatible) and sterile clones was investigated. Results. Fertile male gametophyte development was accompanied by two peaks of ethylene production by anther tissues during microspore development and pollen grain maturation. In sterile line, tenfold higher ethylene production was observed at the meiosis stage and correlated with degeneration of both microsporocytes and tapetum. The male gametophyte germination, both in vitro and in vivo, was accompanied by an increase in ethylene production. The male gametophyte germination after self-incompatible pollination was accompanied by a higher level of ethylene production as compared to compatible pollination. Conclusions. These results suggest that ethylene is an important factor of male gametophyte development, germination, and growth at the progamic phase of fertilization.